Preparation of solid lipid nanoparticles containing active compound by electrohydrodynamic spraying - Eltayeb, M; Bakhshi, P; Stride, E; Edirisinghe, M (2013)
Electrohydrodynamic (EHD) processing and forming has been successfully used to encapsulate a range of active ingredients but its application in flavour enhancement has been very limited. In this study, an EHD method is used for the first time to prepare nanosized particles of solid lipids, i.e. stearic acid and ethylcellulose encapsulating maltol flavour. The weight ratio of stearic acid: ethylcellulose was kept at 5. Particles, which were spherical in shape and 10-100. nm in diameter, were obtained with stable jetting with the applied voltage set to 13-15. kV and using flow rates of 10 and 15. μl/min. The maltol encapsulation efficiency and yield were 69.5% and 69%, respectively. Fourier transform infrared spectroscopy confirmed the presence of maltol within the stearic acid-ethylcellulose matrix, without any chemical interaction between ingredients. © 2013 Elsevier Ltd.